USE OF MODERN METHODS OF IDENTIFICATION OF HYDROCARBON CONTAINING MICROORGANISMS ISOLATED FROM THE MARINE ENVIRONMENT OF THE CASPIAN SEA - Zhanna Musayeva,; Erbol Musayev,; Symbat Koibakova,; Syrlybekkyzy Samal, (Academic Journal of Physical and Chemical Sciences, 2020)
. Currently, the problem of the negative impact of petroleum hydrocarbons in the Caspian Sea has become catastrophic. Intensive pollution of marine waters by oil and oil products, from production, transportation and storage of hydrocarbons leads to the oppression of the sea ecosystem. Mechanical and physico-chemical methods for cleaning the marine environment are characterized by low efficiency, secondary pollution and high cost. The most promising is the use of microbiological methods for cleaning waters from oil pollution. In the article presents the results of the identification of reactive oxidizing bacteria isolated from the marine environment of the Caspian Sea, for further use in new biopreparation from oil pollutions. From the sea water in bulk berths Aktau sea port and the port of Bautino (North Caspian) allocated 27 hydrocarbon isolates of microorganisms having the ability to oil degradation of these strains selected the 4 most active cultures, which were identified as Bacillus cereus (2 strains), strain Bacillus sr.13 and Acinetobacter sr.10. Article is written by results of the scientific project of grant financing of Committee of Science of the Ministry of Education and Science of the Republic of Kazakhstan "Activization of the self-clearing ability of sea water of the Caspian Sea from oil products". Article is issued thanks to the international project Tempus of IV IEMAST of "Establishing Modern Master-level Studies in Industrial Ecology".